La psicoterapia nei servizi pubblici. Introduzione - Masini, Andrea (Il sogno della farfalla, 2020)
This article introduces a monographic issue which describes some significative psychoterapeutic experiences in the public services. The author also analyses a number of theoretical reflections and practical issues raised by this clinical practice.